PENINGKATAN HASIL BELAJAR PKn SISWA MENGGUNAKAN MODEL PICTURE AND PICTURE DI KELAS V SDN 09 BELAKANG BALOK BUKITTINGGI - Syarif, Ahmad; Reinita, Reinita; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
ABSTRACT The purpose of this research was to improve the student learning outcomes in the Civics learning  used Picture And Picturein grade V elementary school. Types of this research was classroom action research with qualitative and quantitative approach. Subject of this research were teacher and students of  V grades were 26. Research conducted in two cycles. The research procedure includes planning, implementation, observation, and reflection. The result of this research I to II cycle.  (a) Lesson plan. The cycle of I was 89% increased to 96% in the II cycle. (b) Implementation, teacher’s activity of I cycle was 86,5% increased to 98%. Students activity of I cycle had averaged was 75% increased in the cycle was 95%. (c) The students learning outcomes in the I cycle was 73 increased to II cycle was 85. Therefore, Picture And Picture appoach can increase the students learning outcomes in the Civics learning in the V grade of elementary school of 09 Belakang Balok, Bukittinggi Keyword : Learning Outcomes ; PKn ; Picture And Picture Model